2016
DOI: 10.5812/numonthly.30598
|View full text |Cite
|
Sign up to set email alerts
|

Early Stent Removal After Kidney Transplantation: Is it Possible?

Abstract: BackgroundThe most important surgical complications of renal transplantation are stenosis and obstruction of the ureterovesical anastomosis. Routine use of ureteral stents can prevent this complication, but the optimal time for ureteral stent use is still controversial.ObjectivesThe purpose of this study is to compare the benefits and complications of early and delayed stent removal after surgery. Early ureteral stent removal can decrease some complications, such as urinary tract infections (UTIs), bladder irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Of the 1043 articles identified from the initial literature search, fourteen articles were within the scope of this systematic review; three randomised controlled trials (RCTs) [20,21,31], nine retrospective cohort studies [8,13,19,22,23,32,33,34,35] and two prospective studies [36,37]. A total of 3216 patients were included, of which 2406 patients (74.8%) underwent living donor KTx (two studies did not record if they used living or deceased donors [34,35]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 1043 articles identified from the initial literature search, fourteen articles were within the scope of this systematic review; three randomised controlled trials (RCTs) [20,21,31], nine retrospective cohort studies [8,13,19,22,23,32,33,34,35] and two prospective studies [36,37]. A total of 3216 patients were included, of which 2406 patients (74.8%) underwent living donor KTx (two studies did not record if they used living or deceased donors [34,35]).…”
Section: Resultsmentioning
confidence: 99%
“…We could not specify the type of stent in five studies. The authors of these five papers were contacted, but unfortunately, we received no response [19,34,35,36,37]. All studies reported the age of the recipients, except for the preliminary results in the three included abstracts [34,35,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Por lo tanto, la relación TAC C / D puede ayudar a los médicos de trasplantes de una manera simple para individualizar el régimen inmunosupresor 25 . Por lo que, es necesario más investigaciones en este aspecto clínico-práctico en nuestro medio.…”
Section: Dosajeunclassified